P PENGARUH PEMBERIAN PENDIDIKAN KESEHATAN PROGRAM ISI PIRINGKU TERHADAP TINGKAT PENGETAHUAN IBU HAMIL - Alit Suwandewi; Hiryadi Hiryadi; Miranti Rahayu (Journal of Nursing Invention, 2021)
Background: Nutritional status is the expression of a state of balance in the form of certain variables or the manifestation of nutriture in the form of certain variables. Nutritional status is very important for pregnant women because it has a very large effect on fetal development and growth. Objective: This study is to determine the effect of providing health education on the plate content program on the level of knowledge of pregnant women in the working area of the Pekauman Health Center. Method: This research is a Pre Experimental design using the One Group Pre test - Post test design conducted in June 2021 with the intervention of providing health education on the contents of my plate program. Data were collected using a questionnaire and analyzed using the Wilcoxon Test Statistical Test. The sample in this study were 65 pregnant women in the Pekauman Health Center Working Area. The sampling technique was purposive sampling. Results: At the level of knowledge of pregnant women before and after the P value is 0.000 <0.05, thus it can be concluded that there is an effect of providing health education on the contents of my plate program on the level of knowledge of pregnant women. Pregnant women are expected to increase information related to the balanced nutrition program (contents of my plate) and understand about the portion of a day's meal so that mothers and babies are healthy and can prevent anemia in pregnancy. Suggestion: Health services are expected to further improve health services, especially providing health education on the contents of my plate program for pregnant women.